Late Abortion: A Comprehensive Review - Sheng Chiang (Elsevier, 2005)
Late termination of pregnancy (LTOP) is defined as an abortion carried out beyond 24 gestational weeks, when the fetus has arguably attained viability. In Taiwan, the current abortion law, bearing a eugenic title, allows LTOP on certain medical grounds. However, the fetal and maternal conditions that constitute medical grounds are not clarified and remain legally untested. Professional debate on the abortion issue is also lacking in academia in Taiwan, despite societal concerns. With the advent of technology to detect fetal abnormalities, obstetricians are now confronted more frequently with acute dilemmas regarding LTOP. Quite often, they sail in an uncharted sea with no clinical guidelines from their professional societies or affiliated hospitals. Recently, LTOP at 35 gestational weeks for a fetus with Down syndrome, complicated with polyhydramnios and tetralogy of Fallot, triggered media scrutiny and aroused much public attention. Although the clinical decision making for pregnancies with fetal abnormalities entails increasingly balanced information and consideration in terms of the medical, ethical, legal, psychologic, and societal aspects, society at large is unaware of the complexity and intertwined nature of various abortion issues, especially LTOP. Obstetricians are now in a vulnerable position in Taiwanese society, where litigations relevant to the practice of early abortions are not rare. Therefore, a global and in-depth look into abortion issues from legal and ethical dimensions is indispensable for modern obstetric practice. This review considers the core issues in LTOP, including what conditions constitute a "serious" fetal abnormality to justify LTOP, the incidence of LTOP, legislation regarding LTOP in Western countries, and recent research on ambivalent fetal pain. It will also present procedures, some under the auspices of the ethical committee of a Presbyterian hospital in Taiwan, for clinical decision making, particularly when abortions are considered in the third trimester.